Pelatihan Dan Pendampingan Penyusunan PTK Dan Publikasi Ilmiah Bagi Guru Madrasah Di Kota Mataram Dan Lombok Barat - M. Harja Efendi; Hanafi (AL HAYAT: Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to increase the understanding and abilities of science teachers in Mataram City and West Lombok Regency regarding PTK. This training activity took place at MTs Miftahul Islah Mataram City and Mts Darul Quran Bengkel West Lombok which was attended by 25 science teachers in Mataram City and West Lombok Regency who were members of the Science Subject Teachers' Conference (MGMP). Activities are carried out using lecture, question and answer, discussion and mentoring methods when preparing proposals. The conclusion from the results of this community service activity is that training and assistance in preparing PTK proposals for science teachers in Mataram City and West Lombok Regency has been carried out smoothly and received a positive response from the participants. This training has provided information for teachers about preparing PTK proposals. In this way, teachers are able to understand and prepare classroom action research proposals. After this training, teachers are expected to be able to make classroom action research proposals and carry out classroom action research to overcome various problems in their class.